Pengaruh Persepsi Kebermanfaatan dan Kemudahan Terhadap Kecemasan Berkomputer Guru SMK Jurusan Akuntansi dalam Mengajar Praktikum Akuntansi Pemerintah - Agus Kuntoro; Yanto Darmawan (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2022)
This research is important because the acceptance of the Siskeudes V.2 application by teachers will determine the success of teachers in teaching. The purpose of this study was to determine the effect of perceived of ease and perceived usefulness of the village financial system software (Siskeudes V.2) on computer self-efficacy of vocational high school teachers. This research was a quantitative research, data was obtained through questionnaires from vocational high school teachers who taking the course of Siskeudes V.2. Data were analyzed by Partial Least Square (PLS) using Smart PLS 3.0. Results of this study are perceived ease of use and perceived usefulnes affects computer anxiety vocational high school teachers. Most of the 29 respondents stated that the benefits of training using the software needed for training according to the needs and perceptions of usefulness required. The results showed that the value of R2 = 39%, meaning that 39% of the variance of computerized vocational school teachers' computerized anxiety regarding the Siskeudes V.2 application was influenced by the variables perceived usefulness and perceived convenience. The results of testing the hypothesis are supported at alpha 5% with T Statistics values ​​H1=2,1519 and H2=1,7398 which values ​​are already above 1,64 for the one-tailed hypothesis.This research makes a practical contribution to the implementation of training in the use of software applications that the training should aim to create perceptions of ease and perceived usefulness so that it is expected to produce a low impact of computer anxiety.